Use of Hyaluronan in the Selection of Sperm for Intracytoplasmic Sperm Injection (ICSI): A Systematic Review and Meta-Analysis - Wei Fan; Weixia Guo; Qiong Chen (Clinical and Experimental Obstetrics & Gynecology, 2024)
Background: Studies on the effect of intracytoplasmic injection of hyaluronan-bound spermatozoa (HA-ICSI) on infertility are insufficient, and its use in treating patients remains controversial. Therefore, we aimed to determine the effectiveness of HA-ICSI in couples with infertility. Methods: A systematic literature review and meta-analysis were conducted to explore the effect of HA-ICSI on couples with infertility. All studies were examined using relative risks (RR) with 95% confidence intervals (95% CI). Results: A total of 1174 publications were retrieved, of which 16 (10 randomized controlled trials (RCTs), five cohort trials, and one publication, including an RCT and a cohort trial) were considered eligible for inclusion. Meta-analysis of the cohort studies indicated a significant advantage for HA-ICSI in terms of live birth rate (LBR), clinical pregnancy rate (CPR), biochemical pregnancy rate (BPR), implantation rate (IR), fertilization rate (FR), and good-quality embryo rate. No difference in spontaneous abortion rate (SAR) or cleavage rate between the HA-ICSI and conventional intracytoplasmic sperm injection (ICSI) groups was observed. Based on the pooled results of all available studies and RCTs, SAR was significantly reduced in the HA-ICSI group than in the conventional ICSI group. The benefits of CPR, IR, and FR were recognized in the pooled results of all available studies; however, RCT analysis did not demonstrate these benefits. Conclusions: The cohort studies indicated a significant advantage of HA-ICSI in terms of LBR, CPR, BPR, IR, FR, and good-quality embryo rates. In RCTs, HA-ICSI significantly reduced the SAR compared to conventional ICSI. Further RCTs with larger sample sizes are required to confirm the beneficial effects of HA-ICSI.